At Speed : My Life in the Fast Lane - Cavendish, Mark (London Ebury Press, 2013)
Mark Cavendish is the first British cyclist to win the Tour de France's green jersey, the first to wear the iconic rainbow jersey in almost 50 years and our only ever rider to capture the Giro d'Italia points title. He is the most prolific sprinter in the Tour's history, and, according to L'Equipe, the best sprinter of all time. But smashing records and racking up victories means whole new levels of fame: and this has come at a price. Living in the goldfish bowl, he has come under fire for his bombastic riding style and been portrayed as everything from an outlaw to a psychopath. Joining Sky in 2012, Cav soon found his own sprint interests to be incompatible with the team's other goals, while the expectations of a nation made his London Olympic failure hard to take. In 'At Speed' Cav takes you through the highs and lows of it all in intimate detail.
Include Color Illustrations.
Mark Cavendish's Life in the Fast Lane.
Keywords: Cavendish, Mark -- Bicycle racing -- Great Britain -- Cyclists